Food-borne zoonotic echinococcosis: A review with special focus on epidemiology - Alvi, Mughees Aizaz; Alsayeqh, Abdullah F. (Frontiers in Veterinary Science, 2022)
Echinococcosis is a WHO listed neglected cyclozoonotic parasitic disease caused by a number of species belonging to genus Echinococcus. The disease is widely distributed across the globe causing heavy economical losses to the farmers and cystic disease in aberrant human hosts. In this review paper, taxonomy, a brief history, magnitude of economic losses, host spectrum and life cycle, risk factors, clinical manifestations are briefly discussed. Furthermore, copro- and sero-ELISA based prevalence of echinococcosis in different continents have been summarized. Last but not least, authors have reviewed the molecular markers based prevalence and applications of molecular epidemiology in taxonomy of Echinococcus species. This review will serve as a quick reference to Echinococcus.